Smart On‐Off Switching Luminescence Materials with Reversible Piezochromism and Basichromism. Issue 28 (9th October 2017) - Yang, Wei; Liu, Chunlin; Lu, Shuang; Du, Jinya; Gao, Qingyun; Zhang, Ronghua; Liu, Yi; Yang, Changying
Abstract: Three novel smart fluorescent on‐off materials based on hemicyanine, 3‐(2‐((1E, 3E)‐4‐(3‐(4‐Fluorophenyl)‐1‐isopropyl‐1H‐indol‐2‐yl)buta‐1, 3‐dien‐1‐yl)naphtho[1,  2‐d]thiazol‐1‐ium‐1‐yl)propane‐1‐sulfonate (NTPS‐FPI ), (E)‐3‐(2‐(2‐(2‐hy‐droxynaphthalen‐1‐yl)vinyl)naphtho[1,  2‐d]thiazol‐1‐ium‐1‐yl)propane‐1‐sulfonate (NTPS‐HN ) and (E)‐2‐(2‐(2‐hydroxynaphthalen‐1‐yl)vinyl)‐1, 1, 3‐trimethyl‐1H‐benz‐o[e]indol‐3‐ium iodide (BI‐HN ), have been developed. They exhibit red or near‐infrared (NIR) emission and tunable on‐off solid‐state luminescent switch by multi‐stimuli, including physical or chemical mode. Single crystal, powder X‐ray diffraction, differential scanning calorimetry and scanning electron microscopy studies provide deep insight on polymorphism‐dependent piezochromism mechanism. Intriguingly, NTPS‐HN andBI‐HN show reversible solid‐state fluorescent on‐off characteristics by exposing in acid‐base vapor, which are ascribed to chemical deprotonation/protonation of terminal hydroxyl group. On the basis of multi‐stimuli response, the dual molecular level basic logic gates are established by using the appropriate external stimulus channel as the inputs and fluorescent colors as the readout data. Abstract : Three novel smart luminescent on‐off materials, NTPS‐FPI, NTPS‐HN and BI‐HN, were synthesized. Their piezochromism and basichromism mechanisms modulated by physical packing and chemical deprotonation were described in detail. On the basis of the multi‐stimuli response, the dual molecular level basic logic gates were established by using the appropriate external stimulus channel as the inputs and luminescence colors as the readout data.